Interaction of Duloxetine Hydrochloride with Deoxyribonucleic Acid Measured by Fluorescence Spectroscopy (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Interactions with many clinically active therapeutic agents with DNA are well studied and it is necessary to decipher the structure of DNA and to investigate the pathological implications of those molecules in living organism. This study investigated the interaction of antidepressant drug Duloxetine-hydrochloride (DLX) with calf thymus DNA (ct-DNA). The interaction of DLX with ct-DNA was studied employing fluorescence spectroscopy. Hypochromic effect was found in the absorption spectra of duloxetine, and its wavelength had no shift in the presence of DNA indicating external binding mode of duloxetine to DNA. Fluorescence spectroscopic results showed the quenching of fluorescence intensity of DLX in presence of DNA indicating the interaction between DLX and DNA. Hydrophobic interaction and hydrogen bonding played the dominating role in DLX-DNA binding and binding forces also indicate the binding site of duloxetine to be at the minor groove of DNA.Dhaka Univ. J. Pharm. Sci. 14(2): 199-206, 2015 (December)